Is fibromyalgia accompanying Behçet’s disease more severe than primary fibromyalgia? - Ayar, Koray; Metin Ökmen, Burcu; Altan, Lale; Kösegil Öztürk, Esra (The European Research Journal, 2020)
Objectives: Although there are studies in the literature about how Behçet’s disease is affected in the presence of fibromyalgia, there is no information about how the severity of fibromyalgia is in the presence of Behçet’s disease. This study aims to evaluate the severity of fibromyalgia by comparing the impact of fibromyalgia and pain thresholds between fibromyalgia patients with and without Behçet’s disease. Methods: Twenty-five fibromyalgia patients with Behçet’s disease and 34 primary fibromyalgia patients were included in this cross-sectional study. All participants completed the fibromyalgia impact questionnaire, and pain thresholds were measured at 18 tender points using algometry. Results: The mean fibromyalgia impact questionnaire scores in fibromyalgia patients with and without Behçet’s disease were 66.6 ± 18.4 and 60.4 ± 14.5, respectively (p = 0.157). Pain thresholds were not different between the groups in 15 of the 18 tender points (TP). In fibromyalgia patients with Behçet’s disease, pain thresholds in TP-15, TP-16 and TP-17 were 11.44 ± 4.84, 11.92 ± 5.00 and 15.16 ± 4.89 pounds, respectively, while in primary fibromyalgia patients those were 8.41 ± 2.68, 8.14 ± 2.76 and 12.14 ± 4.06 pounds respectively. Pain thresholds in TP-15, TP-16 and TP-17 were significantly different between the groups (p = 0.003, p = 0.003, p = 0.014, respectively). Conclusions: According to the literature data, although fibromyalgia has an effect on Behçet’s disease, especially in cases associated with central sensitization syndromes, the severity of fibromyalgia was not found to be different in fibromyalgia patients with and without Behçet’s disease in this study. There may be a relationship between Behçet’s disease and fibromyalgia due to non-inflammatory causes such as central sensitization.